A far-UV survey of three hot, metal-polluted white dwarf stars: WD0455−282, WD0621−376, and WD2211−495. Issue 3 (4th June 2019) - Preval, Simon P; Barstow, Martin A; Bainbridge, Matthew; Reindl, Nicole; Ayres, Thomas; Holberg, Jay B; Barrow, John D; Lee, Chung-Chi; Webb, John K; Hu, Jiting
ABSTRACT: Using newly obtained high-resolution data ( R ∼ 1 × 10 5 ) from the Hubble Space Telescope, and archival UV data from the Far Ultraviolet Spectroscopic Explorer, we have conducted a detailed UV survey of the three hot, metal-polluted white dwarfs WD0455−282, WD0621−376, and WD2211−495. Using bespoke model atmospheres, we measured T eff, log g, and photospheric abundances for these stars. In conjunction with data from Gaia, we measured masses, radii, and gravitational redshift velocities for our sample of objects. We compared the measured photospheric abundances with those predicted by radiative levitation theory, and found that the observed Si abundances in all three white dwarfs, and the observed Fe abundances in WD0621−376 and WD2211−495, were larger than those predicted by an order of magnitude. These findings imply not only an external origin for the metals, but also ongoing accretion, as the metals not supported by radiative levitation would sink on extremely short time-scales. We measured the radial velocities of several absorption features along the line of sight to the three objects in our sample, allowing us to determine the velocities of the photospheric and interstellar components along the line of sight for each star. Interestingly, we made detections of circumstellar absorption along the line of sight to WD0455−282 with three velocity components. To our knowledge, this is the first such detection of multicomponent circumstellar absorption along the line of sight to a white dwarf.